Dimerization of Oxazolones by Copper-Catalyzed Cross-Dehydrogenative Coupling Reactions - Hai, Pham Thi Hong; Anh, Le Duc; Tu, Ha Minh (VNU Journal of Science: Natural Sciences and Technology, 2025)
A convenient and efficient cross-dehydrogenative coupling reaction by using readily available and inexpensive copper catalyst was reported. Several oxazolone derivatives underwent dimerization via the formation of C sp3 -C sp3 bond under oxidative conditions in the presence of copper(II) acetate as a catalyst, di- tert- butyl peroxide as an oxidant, potassium carbonate as a base, and at high temperature. The dimerized products containing two quaternary centres were obtained in moderate to good yields, suggesting an approach to the synthesis of non-proteinogenic amino acids.